Criminal Liability for Human Abduction - Vyacheslav N. Voronin (Сибирское юридическое обозрение, 2017)
The Author considers the quality of the construction of the criminal law provision which is stipulated in article 126 of the Criminal Code of Russian Federation (Kidnapping). The Author signifies some application problems of the concerned article, researches judicial interpretations of the elements of crime characteristics and opinions of contemporary scientists who propose to redraft the article. The Author also analyses the law of Armenia, Belarus, Kyrgyzstan, Turkmenistan, Tajikistan and Latvia. On the basis of the research the Author concludes that a primitive disposition which doesn’t include elements of a criminal conduct doesn’t meet the requirements of legality and legal certainty, and, because of the above-mentioned reason, the Author proposes his own definition of the disposition of kidnapping.